Penyelenggaraan Tridharma Perguruan Tinggi sesuai Bidang Keilmuan Sebagai Upaya Personal Branding Dosen - A. Dian Fitriana; Iin Mutmainnah; Syarifa Halifah (KOMUNIDA : Media Komunikasi dan Dakwah, 2021)
The main task of a lecturer is to carry out the There Pillars of Higher Education which includes teaching, research and community service. Ideally, while carrying out these three pillars, lecturers should have qualified educational background to be recognized as a competent lecturer. The existence of competencies in accordance with the scientific field in carrying out the Three Pillars of Higher Education will indirectly provide an identity, distinctiveness and brand for a lecturer. The purpose of this study is to explain and describe how the implementation of the Thee Pillars including teaching, research and community service by a lecturer in terms of building uniqueness and identity through personal branding. The method used in this study is a qualitative descriptive approach using interview and observation techniques to several lecturers at the State Islamic Institute (IAIN) Parepare. The results of this research show that in terms of teaching, there are still lecturers who carry out teaching functions that are not in accordance with their knowledge for various reasons, which have a huge impact on the level of effort to build uniqueness (personal branding). The same thing is also found in the research function, but in this section there are several lecturers who feel that they do research not based on science but according to their passion. Not much different from teaching and research, in the function of community service, the same thing is also found. Another finding is that a lecturer conducts community service by lecturing or preaching. This phenomenon happens because of the reason that they come from an Islamic campus so they are required to do service by means of preaching.